Radiation Hardness of Flash Memory Fabricated in Deep-Submicron Technology - Bojan Cavrić; Edin Dolićanin; Predrag Petronijević; Milić Pejović; Koviljka Stanković (International Journal of Photoenergy)
This paper discusses the current problem of the electronic memory reliability in terms of the ionizing radiation effects. The topic is actual since the high degree of components' miniaturization integrated into the flash memory causes the extreme sensitivity of this memory type to the ionizing radiation effects. The effects of ionizing radiation may cause changes in stored data, or even the physical destruction of the components. At the end, the experimentally and numerically obtained effects of radiation on specific flash memories are shown and discussed. The results obtained by laboratory and numerical experiments showed good agreement with each other and with the theoretically expected results.